SISTEM INFORMASI ARSIP DI BADAN PUSAT STATISTIK PROVINSI SUMATERA BARAT BERBASIS MOBILE - Kurnia Wahyu Prima; Elfi Tasrif (Universitas Negeri Padang, 2019)
Activities in both government and private agencies require data and information, one of which is archived. Archive is an important factor that supports the smooth running of activities in the agency. The archive information system is created efficiently and effectively with a mobile application based that aims to help users manage archives. In making this information system, Android Studio assistance software is used as a software maker program and Corel Draw as an application design maker. The method used in this application is the waterfall method. The waterfall method is a sequential design process that is often used in software development, the process continues to flow downward like a waterfall through several stages namely system requirements analysis, system design, coding and finally testing. From these problems and methods produced an archive information system that aims to facilitate its users in managing records.Keywords: Information system, Archive, Android Studio, Waterfall